2009
DOI: 10.1245/s10434-009-0544-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Laser-Induced Thermal Therapy for Small Palpable Invasive Breast Carcinomas: A Feasibility Study

Abstract: BackgroundThe next step in breast-conserving surgery for small breast carcinomas could be local ablation. In this study, the feasibility of ultrasound-guided laser-induced thermal therapy (LITT) is evaluated.MethodsPatients with large-core needle biopsy-proven invasive, palpable breast carcinoma (clinically ≤2 cm) underwent ultrasound-guided LITT, followed by surgical excision. Completeness of ablation was determined by both hematoxylin and eosin staining and nicotinamide adenosine diaphorase staining.ResultsF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…6,12,18,26,29,30,36 Energy in the form of light is emitted through a saline-or water-cooled catheter and converted to thermal energy within the target tissue. 10,37 The resulting thermal coagulation and damage to intracellular proteins and DNA ultimately leads to cell death.…”
mentioning
confidence: 99%
“…6,12,18,26,29,30,36 Energy in the form of light is emitted through a saline-or water-cooled catheter and converted to thermal energy within the target tissue. 10,37 The resulting thermal coagulation and damage to intracellular proteins and DNA ultimately leads to cell death.…”
mentioning
confidence: 99%
“…A total of 63 articles matched the selection criteria. The 63 articles included 16 feasibility studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], 12 phase I studies [29][30][31][32][33][34][35][36][37][38][39][40], nine phase II studies [41][42][43][44][45][46][47][48][49], three comparative studies [50][51][52], one retrospective study [53], and four randomised controlled trials [54][55][56]. In 18 studies the type of study was not reported [8,[57][58][59][60][61][62][63][64]…”
Section: Selected Studiesmentioning
confidence: 99%
“…The ablation process involves two phases: freezing and thawing with four mechanisms destroying the tumour cells: direct damage by intracellular ice formation and osmotic dehydration and indirect damage due to ischemia and immunologic response. [36,78] Seven studies used laser-ablation (231 patients) [18,28,33,34,50,62,63], in which lesions are ablated due to direct heating with low-power laser light energy delivered percutaneously via thin optical fibres. Upon absorption in the tissue, heat is produced, inducing lethal thermal injury.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[36][37][38] The light is both scattered and absorbed by the tissue. The absorption events are primarily near the laser and result in large heating near the laser applicator.…”
Section: Laser Ablationmentioning
confidence: 99%